The Prevalence of Cardiovascular Diseases and associated factors among patients in Low- and Middle-Income settings - RWEYEMAMU, SAMWEL JACOB; Longopa, George L.; Bishashara, Sophia; Mpellah, Rosemary G; Mutagaywa, Reuben; Waane, Tatizo; Kisenge, Peter Richard (European Journal of Applied Sciences, 2022)
Background Cardiovascular Diseases (CVDs) are the public health problems worldwide, causing over 18.9 million deaths per year. The major risk factors which are also preventable are tobacco use, diabetes, high blood pressure, overweight/ obesity and alcohol consumption. The aim of this study was to determine the Prevalence of CVDs and associated factors. Methodology We conducted a cross-sectional hospital-based study that consecutively enrolled 785 consenting adults who came to attend Jakaya Kikwete Cardiac Institute (JKCI) mobile clinic in South Western urban Tanzania, a typical LMIC, in 2018. A structured questionnaire was used to obtain demographic data and gather several co-morbid information. A 12 lead Electrocardiogram (ECG) and 2D, M mode Transthoracic Echocardiogram were done to determine the structural and none structural heart diseases from the participants. Results Of 785 participants, 528 (67.3 %) were females, 479 (61%) were middle aged (40-60 years) and 196 (25%) were 65 years old and above, their mean age (±SD) was 56 (±14) years. Most of participants were married 558 (71%), 625 (80%) sponsored by the National Health Insurance Fund (NHIF) and less than half were employed. Of all the participants, tobacco users were 29(3.6%), diabetics 60 (7.5%), alcoholic users 99 (12.5%) and more than half were overweight/obese. The prevalence of Systolic Hypertension was 65% and Diastolic Hypertension was 50% Few participants 85 (11%) had chest pain, 56 (7%) had tachycardia and difficulty in breathing 45 (6%). By ECHO diagnosis; the prevalence of dilated cardiomyopathy was 3.8%, hypertensive heart diseases 2.3% and valvular heart diseases was 2%. Majority 780 (99%) and 694 (88%) had normal Left Ventricular Systolic and Diastolic functions respectively. Furthermore, by ECG diagnosis, the prevalence of Left Ventricular Hypertrophy was 8% and ischemic heart disease was diagnosed in 4% of the participants. In a multivariate analysis, CVD were found to be statistically significant associated with the age 65+ years, 3.41 [95% CI 1.49 -7.78, p- value 0.004], diastolic blood pressure above or equal to 90 mmHg, 1.61 [95% CI 1.05 -2.48, p -value 0.03] and overweight/ obese 1.94 [95% CI 1.28 -2.92, p-value 0.002]. Conclusion The prevalence of cardiovascular diseases was found to be high and the main associated risk factors were advanced age, overweight/obese and diastolic hypertension. Some of the participants had already developed asymptomatic structural heart disease and features which were suggesting of coronary artery diseases. Recommendations Efforts for an early detection of CVD should be undertaken in order to offer an early and appropriate interventions